2013
DOI: 10.1007/s00062-013-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Primary Central Nervous System Lymphomas from High-Grade Gliomas by rCBV and Percentage of Signal Intensity Recovery Derived from Dynamic Susceptibility-Weighted Contrast-Enhanced Perfusion MR Imaging

Abstract: The combination of rCBV measurement with percentage of signal intensity recovery can help in more accurate differentiation of PCNSL from HGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 37 publications
2
48
0
2
Order By: Relevance
“…PCNSL has been shown to have lower vascularity and higher permeability than glioblastoma. 7,14,19,20,25 These differences are considered to reflect their histological changes. PCNSL lacks abundant neovascularisation, but grows angiocentrically and tends to cluster around preexisting brain vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNSL has been shown to have lower vascularity and higher permeability than glioblastoma. 7,14,19,20,25 These differences are considered to reflect their histological changes. PCNSL lacks abundant neovascularisation, but grows angiocentrically and tends to cluster around preexisting brain vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The PSR can be measured by using either signal intensity at the end of the first-pass 19 or mean signal intensity after the first-pass. 16,20 In some cases, signal intensity continues to recover or increase after the first-pass, and measurement points can be varied. 9,21 Meanwhile, the present authors' analysis of signal intensityetime curves, the slopes during the first-pass (i.e., drop and rise) of PCNSL seem to be different from those of glioblastoma; therefore, this slope ratio can be useful as a simple index for tumour differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Peak height of the ΔR2/ΔR2* curve correlates well with rCBV, though the area under the relaxivity–time curve is the most commonly used measure for rCBV. PSR has been shown to differ in high-grade glioma, lymphoma, and metastases, 5,98 probably due to physiologic differences in vascular permeability and tumor cell size and cell volume fraction for these tumors and the complex interaction of these factors on the T1- and T2*-weighting of DSC-MRI signal. The signal–time curve tends to return closer to baseline with high-grade glioma than with metastases, presumably due to the absence of the blood-brain barrier and dominant T2/T2* effects of “pooled” gadolinium in the latter.…”
Section: F) Interpretation Guidelines For Neoplasmsmentioning
confidence: 99%
“…The potential of an nCBV or rCBV as a reliable index of GBM or PCNSL diagnosis has been reported several times (5,(7)(8)(9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20)(21). According to a previous report using the maximum, the mean or the median value of nCBV, GBM has a significantly higher nCBV value compared to PCNSL (5, 7-10, 13-21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dynamic susceptibility contrast-enhanced (DSC) perfusion MR imaging (PWI) analysis is a reliable way to differentiate GBM from PCNSL, and especially, the relative cerebral blood volume (rCBV) from DSC PWI, which reflects microvascular density and angiogenesis, is the most important hemodynamic parameter for a differential diagnosis of GBM and PCNSL (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%